The Role of Lavender in Wound Healing: A Review of Clinical, in Vivo, and in Vitro Studies - Karinnia Karinnia; Linda Julianti Wijayadi; Kelvin Kelvin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Wound healing is a dynamic and complex biological process involving haemostasis, inflammation, proliferation, and tissue remodelling. Disruption of any phase can lead to delayed healing or chronic wounds, the number of which is increasing nowadays. This give rise to growing interest in natural products, particularly essential oils as complementary wound-care agents. This literature review summarizes recent evidence (2015–2025) from in vitro, in vivo, and clinical studies evaluating the wound-healing effects of lavender (Lavandula angustifolia) and related species. Literature searches and screening were conducted in PubMed, SpringerLink, ProQuest, and Google Scholar from 2015 to 2025 using specific keywords. A total of 7,068 studies were retrieved, and after screening, 5 studies were included. Findings indicate that lavender, largely through its major constituents linalool and linalyl acetate, exhibits antioxidant, antimicrobial, and anti-inflammatory properties that support granulation, re-epithelialization, and collagen remodelling. Advances in formulation are further enhancing the therapeutic efficacy of lavender, but clinical evidence remains limited and heterogeneous. Trials with standardized doses and formulations are needed to elucidate the effectiveness of lavender, particularly in wound management.